Early Graft Loss After Kidney Transplantation: Risk Factors and Consequences. Issue 6 (23rd February 2015) - Hamed, M. O.; Chen, Y.; Pasea, L.; Watson, C. J.; Torpey, N.; Bradley, J. A.; Pettigrew, G.; Saeb‐Parsy, K.
<x xml:space="preserve">Abstract</x> Early graft loss (EGL) after kidney transplantation is a catastrophic outcome that is assumed to be more likely after the use of kidneys from suboptimal donors. We therefore examined its incidence, risk factors and consequences in our center in relation to different donor types. Of 801 recipients who received a kidney‐only transplant from deceased donors, 50 (6.2%) suffered EGL within 30 days of transplantation. Significant risks factors for EGL were donation after circulatory death (DCD) (odds ratio [OR] 2.88; p = 0.006), expanded criteria donor (ECD) transplantation (OR 4.22; p = 0.010), donor age (OR 1.03; p = 0.044) and recipient past history of thrombosis (OR 4.91; p = 0.001). Recipients with EGL had 12.28 times increased risk of death within the first year, but long‐term survival was worse for patients remaining on the waiting list. In comparison with patients on the waiting list but not transplanted, and with all patients on the waiting list, the risk of death after EGL decreased to baseline 4 and 23 months after transplantation, respectively. Our findings suggest that DCD and ECD transplantation are significant risk factors for EGL, which is a major risk factor for recipient death. However, long‐term mortality is even greater for those remaining on the waiting list.